Lipid Horizons: Recent Advances and Future Prospects in LBDDS for Oral Administration of Antihypertensive Agents - null Preeti; Sharda Sambhakar; Rohit Malik; Saurabh Bhatia; Ahmed Al Harrasi; Renu Saharan; Geeta Aggarwal; Suresh Kumar; Renu Sehrawat; Chanchal Rani (International Journal of Hypertension)
The lipid-based drug delivery system (LBDDS) is a well-established technique that is anticipated to bring about comprehensive transformations in the pharmaceutical field, impacting the management and administration of drugs, as well as treatment and diagnosis. Various LBDDSs verified to be an efficacious mechanism for monitoring hypertension systems are SEDDS (self-nano emulsifying drug delivery), nanoemulsion, microemulsions, vesicular systems (transferosomes and liposomes), and solid lipid nanoparticles. LBDDSs overcome the shortcomings that are associated with antihypertensive agents because around fifty percent of the antihypertensive agents experience a few drawbacks including short half-life because of hepatic first-pass metabolism, poor aqueous solubility, low permeation rate, and undesirable side effects. This review emphasizes antihypertensive agents that were encapsulated into the lipid carrier to improve their poor oral bioavailability. Incorporating cutting-edge technologies such as nanotechnology and targeted drug delivery, LBDDS holds promise in addressing the multifactorial nature of hypertension. By fine-tuning drug release profiles and enhancing drug uptake at specific sites, LBDDS can potentially target renin-angiotensin-aldosterone system components, sympathetic nervous system pathways, and endothelial dysfunction, all of which play crucial roles in hypertension pathophysiology. The future of hypertension management using LBDDS is promising, with ongoing reviews focusing on precision medicine approaches, improved biocompatibility, and reduced toxicity. As we delve deeper into understanding the intricate mechanisms underlying hypertension, LBDDS offers a pathway to develop next-generation antihypertensive therapies that are safer, more effective, and tailored to individual patient needs.